The effects of heavy upper-body strength training on ice sledge hockey sprint abilities in world class players - Sandbakk, Ø.; Hansen, M.; Ettema, G.; Rønnestad, B. (Human Movement Science, 2014)
The current study investigated the effects of 6 weeks of heavy upper-body strength training on maximal strength and sprint abilities in eight world class ice sledge hockey players. Before and after the strength training intervention, all subjects performed a 30-m maximal sprint on ice (where time for each 10 m section was measured) and 1 repetition maximal (1RM) strength test in the bench pull (BP), pull-down (PD), pull over (PO) and front pull (FP) exercises. Three weekly sessions with 3 × 6-8RM for these strength exercises were added during the intervention period. From pre- to post-test, 1RM in the strength exercises improved by 4-8%, whereas 30-m sprint time, all 10-m section times and the calculated power output in the 10-m acceleration phase all improved by 2-3% (all P < .05). The pre- to post-test changes in 30-m sprint time and the initial 10-m time correlated significantly with the changes in 1RM for BP (r = 0.59 and 0.55) and PD (r = 0.60 and 0.68) (all P < .05). In conclusion, the results of this study strongly suggest that heavy upper-body strength training improves upper-body strength and ice sledge hockey sprint abilities, and that the magnitude of improvements in strength correlates with the improvements in sprint abilities.